Cancer Therapy: Biomimetic Diselenide‐Bridged Mesoporous Organosilica Nanoparticles as an X‐ray‐Responsive Biodegradable Carrier for Chemo‐Immunotherapy (Adv. Mater. 50/2020). Issue 50 (15th December 2020) - Shao, Dan; Zhang, Fan; Chen, Fangman; Zheng, Xiao; Hu, Hanze; Yang, Chao; Tu, Zhaoxu; Wang, Zheng; Chang, Zhimin; Lu, Junna; Li, Tianyu; Zhang, Yuan; et al.
Abstract : In article number 2004385, Dan Shao, Kam W. Leong, Wen‐fei Dong, and co‐workers present cancer‐cell‐membrane‐coated mesoporous organosilica nanoparticles for radiation‐responsive drug delivery and cancer chemo‐immunotherapy. Under low‐dose X‐ray radiation, such biomimetic nanotherapeutics exhibit degradation‐controlled drug release and induced stronger antitumor immune responses, leading to enhanced tumor regression and metastasis inhibition with low systematic toxicity when combined with anti‐PD‐L1.